Anti-hyperglycemic and anti-hyperlipidemic effect of poly-herbal formulation in streptozotocin-nicotinamide induced diabetic rats - Gupta A.; Kumar V.; Reddy K.R.C. (My University, 2025)
Introduction: Diabetes mellitus is one of the important metabolic diseases, and the percentage of affected population is increasing day by day. The search for better medicament is the need of hour. Aim: Poly-herbal formulation (PF) containing fourteen plant materials is studied for anti-hyperglycemic and anti hyperlipidemic effect. Material and methods: A total of 36 rats were taken for the study. The rats of either sex randomly divided into five groups, among these five groups, four groups contained 6 animals in each, whereas one group, i.e., normal control groups contain 12 animals. Group one (control) animals were treated with carboxy methyl cellulose, whereas group two animals were treated with streptozotocin (STZ) to induce diabetes. Group three animals were treated with 300 mg dose test drug and group four treated with 600 mg of the test drug. Whereas group five was treated with a known anti-diabetic drug, i.e., glibenclamide 10 mg. Result: It is found that the testing drug PF is a novel medicine having significant anti hyperglycemic effect and anti hyperlipidemic effect. No significant change was found in HDL level. Conclusion: PF is having good antidiabetic effect against STZ-nicotinamide induced model of diabetic rats.